Bias From Nonsynchronous Trading in Tests of the Levhari-Levy Hypothesis - Wood, Robert A.; McInish, Thomas H. (The Review of Economics and Statistics, 1985)
Garbade, Kenneth, Methods of Examining the Stability of Regression Coefficients, Journal of the American Statistical Association 72 (Mar. 1977), 54-63. Godfrey, L. G., Against General Autoregressive and Moving Average Error Models when the Regressors Include Lagged Dependent Variables, Econometrica 46 (Sept. 1978), 1293-1301. Harvey, Andrew C., and Garry D. A. Phillips, for Stochastic Parameters in Regression S.S.R.C. supported project on Testing for Specification Error in Econometric Models, Working Paper No. 1, University of Kent at Cantebury (1976). _ Maximum Likelihood Estimation of Regression Models with Autoregressive-Moving Average Disturbances, Biometrika 66 (1979), 49-58. Johnson, N. L., and S. Kotz, Distribution in Statistics: Continuous Multivariate Distributions (New York: Wiley, 1972). LaMotte, R., and A. McWhorter, Jr., An Exact Test for the Presence of Random Walk Coefficients in a Linear Regression Model, Journal of the American Statistical Association 73 (Dec. 1978), 816-819. Mizon, Grayham E., and David F. Hendry, An Empirical Application and Monte Carlo Analysis of of Dynamic Specification, Review of Economic Studies 47 (Jan. 1980), 21-46. Pagan, Adrian R., Some Identification and Estimation Results for Regression Models with Stochastically Varying Coefficients, Journal of Econometrics 13 (1980), 341-363. Pagan, Adrian R., and K. Tanaka, A Further Test for Assessing the Stability of Regression Coefficients, Australian National University, unpublished manuscript (1979). Quandt, Richard E., Tests of the Hypothesis that a Linear Regression System Obeys Two Separate Regimes, Journal of the American Statistical Association 55 (Dec. 1960), 873-880. Rosenberg, Barr, The Analysis of a Cross-Section of Time Series by Stochastically Convergent Parameter Regression, Annals of Economic and Social Measurement 2 (1973), 399-428. Watson, Mark W., A Test for Regression Coefficient Stability when a Parameter Is Identified only Under the Alternative, H.I.E.R. Discussion Paper 906 (1982). , Applications of Kalman Filter Models in Econometrics, Ph.D. Dissertation, University of California at San Diego (1980). Watson, Mark W., and Robert F. Engle, Alternative Algorithms for the Estimation of Dynamic Factor, MIMIC, and Varying Coefficient Regression Models, Journal of Econometrics 23 (Dec. 1983), 385-400.